2013
DOI: 10.1080/10810730.2012.727949
|View full text |Cite
|
Sign up to set email alerts
|

Underage Drinkers' Responses to Negative-Restrictive Versus Proactive-Nonrestrictive Slogans in Humorous Anti–Alcohol Abuse Messages: Are Humorous Responsible Drinking Campaign Messages Effective?

Abstract: This study examined underage drinkers' responses to negative-restrictive versus proactive-nonrestrictive slogans in humorous anti-alcohol abuse advertisements. The authors conducted a posttest-only control group experiment with 91 teenagers and college-aged participants. For underage moderate drinkers, the negative-restrictive slogans (e.g., "Don't drink") increased participants' perceived risk of excessive drinking and increased a level of intention to change their drinking behavior. However, for underage bin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…This study is the first to comprehensively test the effects of the portrayal of alcohol in audiovisual mass media content on the viewer by manipulating not only alcohol consequences, but also character valence. Furthermore, we included interaction effects with level of alcohol consumption (Kim et al, 2014;Lee & Chen, 2013). In addition, age (an important covariate that has not been thoroughly tested) and gender were included.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study is the first to comprehensively test the effects of the portrayal of alcohol in audiovisual mass media content on the viewer by manipulating not only alcohol consequences, but also character valence. Furthermore, we included interaction effects with level of alcohol consumption (Kim et al, 2014;Lee & Chen, 2013). In addition, age (an important covariate that has not been thoroughly tested) and gender were included.…”
Section: Discussionmentioning
confidence: 99%
“…Effect studies in numerous areas showed that viewers' characteristics influence the effect of mass media (e.g., Lee & Chen, 2013;Stephenson, 2003). In the context of alcohol-related behavior, the viewer's own behavior related to alcohol seems especially crucial.…”
Section: Level Of Alcohol Consumptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Humorous anti-tobacco messages are remembered more than those using normative or sadness/fear appeals among adolescents (Biener et al, 2004). When adolescents and young adults process messages that use fear appeals, they may become defensive; use of humor may offset this response (Lee & Chen, 2013).…”
Section: Phase 3: Message Development and Testingmentioning
confidence: 99%
“…M. J. Lee and Chen (2013) found that effects of proactive-nonrestrictive (directing to drink responsibly) or negative-restrictive (directing to not drink) slogans in humorous anti-binge drinking PSAs depended on whether the respondents were binge drinkers or moderate drinkers. Proactive-nonrestrictive slogans were more effective than negative-restrictive slogans for binge drinkers, however the results for proactive-nonrestrictive messages were similar to the control group.…”
Section: Reactancementioning
confidence: 99%